Calcium acetate-induced linear fixed drug eruption - Coskun, B; Saral, Y; Ozturk, P; Karincaoglu, Y; Cobanoglu, B (Karger, 2005)
[Abstract Not Available]
Keywords: calcium acetate; linear fixed drug eruption